Substitutability and Competition in the Dixit-Stiglitz Model - Winfried Koeniger; Omar Licandro (Institute for the Study of Labor (IZA), 2004)
The effects of competition on growth are analyzed in the recent literature by comparing economies with the same market structure but different degrees of substitutability. In this note, we show that in a general equilibrium model with monopolistic competition – la Dixit- Stiglitz the effect of substitutability on the allocation of resources is independent of the associated change in competition. Higher substitutability increases welfare, output and productivity because resources shift towards the most productive sectors. However, since markups are equal across sectors, changes in market power do not affect the relative price of consumption goods, implying that the induced changes in market power do not have any direct effect on equilibrium allocations.
Keywords: L16; 330; monopolistic competition; substitution; market power; output; Monopolistischer Wettbewerb; Produktsubstitution; Marktmacht; Allgemeines Gleichgewicht; Wirtschaftswachstum; Theorie